Analisis Rantai Pasok Bahan Baku Utama Melinjo Agroindustri Emping di Desa Alaswangi Pandeglang - Putri Sapitri; Isyana Emita (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
The purpose of ithis study iwas ito ianalyze ithe Supply Chain for emping chips in Alaswangi Village, located in Menes District,Pandeglang Regency, Banten. The paradigm in this study is constructivism and uses a qualitative idescriptive approach. Data collectioniwas conducted through field visits and direct interviews with informants. The results of this study indicate that the emping chip Supply Chain in Alaswangi Village, known as Sukses Mulia, is inseparable from the upstream Supply Chain, internal Supply Chain, and downstream Supply Chain. The results of this study indicate that the upstream Supply Chain is related to the supply of raw materials, startingifrom icollectors to melinjo farmers in Saketi,and Menes.Processing into emping chips and selling them raw per kilogram. The internal Supply Chain includes sorting, roasting, shell separation, flattening, drying, and packaging. The downstream Supply Chain includes distribution activitiesito end consumers. The effectiveness and efficiency of the Supply Chain for emping artisans in Alaswangi Village are quite good, but further evaluation of productidevelopment is still needed.